Repositioning FDA-Approved Sulfonamide-Based Drugs as Potential Carbonic Anhydrase Inhibitors in Trypanosoma cruzi: Virtual Screening and In Vitro Studies - Eyra Ortiz-Pérez; Adriana Moreno-Rodríguez; Timoteo Delgado-Maldonado; Jessica L. Ortega-Balleza; Alonzo González-González; Alma D. Paz-González; Karina Vázquez; Guadalupe Avalos-Navarro; Simone Giovannuzzi; Claudiu T. Supuran; Gildardo Rivera (Pharmaceuticals)
Background/Objectives: α-carbonic anhydrase (α-TcCA) has emerged as a promising drug target in T. cruzi, the causative agent of Chagas disease in the Americas. Sulfonamides, known inhibitors of CAs, bind to the zinc ion on the enzyme’s active site. This study proposes the repositioning of sulfonamide-based drugs to identify new trypanocidal agents. Method: Ligand-based virtual screening and molecular docking analysis were performed on FDA-approved drugs targeting α-TcCA. These compounds were evaluated in vitro and ex vivo against the A1 and NINOA strains, followed by enzymatic assays. Results: Four sulfonylureas were selected: glimepiride (Glim), acetohexamide (Ace), gliclazide (Glic), and tolbutamide (Tol). Ace and Tol had half-maximal inhibitory concentration (IC50) values similar or better than reference drugs against the NINOA strain in the epimastigote and trypomastigote stages, while Glic and Glim had the highest activity against the A1 strain (epimastigotes and amastigotes). Notably, Ace had the highest trypanocidal activity against all stages in NINOA, with IC50 values of 6.5, 46.5, and 46 μM for epimastigotes, trypomastigotes, and amastigotes, respectively. Additionally, Ace inhibited α-TcCA with KI = 5.6 μM, suggesting that its trypanocidal effect is associated to the enzyme inhibition. Conclusions: This study supports the repositioning of FDA-approved sulfonamide-based hypoglycaemic agents as trypanocidal compounds. Future studies should focus on structural modifications to improve selectivity. Integrating docking, parasitological, and enzymatic data is crucial for optimizing drug candidates for Chagas disease.